2012
DOI: 10.1007/978-3-642-30241-1_12
|View full text |Cite
|
Sign up to set email alerts
|

I-SEARCH: A Unified Framework for Multimodal Search and Retrieval

Abstract: Abstract. In this article, a unified framework for multimodal search and retrieval is introduced. The framework is an outcome of the research that took place within the I-SEARCH European Project. The proposed system covers all aspects of a search and retrieval process, namely low-level descriptor extraction, indexing, query formulation, retrieval and visualisation of the search results. All I-SEARCH components advance the state of the art in the corresponding scientific fields. The I-SEARCH multimodal search e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Of course, a lot of effort is being made to integrate various elements of interaction and develop new protocols and architectures that allow their use [2,5,8]. In fact, the W3C has a specific group for this work [7,12].…”
Section: State Of the Artmentioning
confidence: 99%
“…Of course, a lot of effort is being made to integrate various elements of interaction and develop new protocols and architectures that allow their use [2,5,8]. In fact, the W3C has a specific group for this work [7,12].…”
Section: State Of the Artmentioning
confidence: 99%
“…The main difficulty in cross-media retrieval is to define a similarity measure among heterogeneous low-level features. In order to simultaneously search and retrieve data from multiple modalities, other approaches have been considered [10,11,12,13,14,15,16,17,18,19,20]. For instance in [16], it is experimentally shown that multimodal queries achieve higher retrieval accuracy than mono-modal ones.…”
Section: Introductionmentioning
confidence: 99%
“…The work in [10] suggests using a combination of ontology browsing and keyword-based querying. The methods presented in [11,14,15,16] use a similar approach and rely on the assumption that every document has an equal number of nearest neighbors for each of the modalities. However, such an assumption might degrade the retrieval performance as a document containing "image+text" may have many nearest neighbors in image modality, but not as many relevant textual data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel unified framework for multimodal search and retrieval by introducing a novel data representation for multimodal data in Content Object (CO) is described in [12]. Recent efforts in the field of multimodal retrieval systems have led to a growing research community and a number of academic and industrial projects.…”
Section: Introductionmentioning
confidence: 99%